2019
DOI: 10.3390/catal9020199
|View full text |Cite
|
Sign up to set email alerts
|

The Support Effects on the Direct Conversion of Syngas to Higher Alcohol Synthesis over Copper-Based Catalysts

Abstract: The types of supports employed profoundly influence the physicochemical properties and performances of as-prepared catalysts in almost all catalytic systems. Herein, Cu catalysts, with different supports (SiO2, Al2O3), were prepared by a facile impregnation method and used for the direct synthesis of higher alcohols from CO hydrogenation. The prepared catalysts were characterized using multiple techniques, such as X-ray diffraction (XRD), N2 sorption, H2-temperature-programmed reduction (H2-TPR), temperature-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…Moreover, the higher alcohols, after separation and purification, can serve as feed stocks for value-added fine chemicals, demonstrating a wide application prospect [4]. Generally, the catalytic production process for higher alcohols synthesis from syngas needs to occur over the solid catalysts, which are roughly classified into the following four categories: modified methanol synthesis catalysts [5,6], modified Fischer-Tropsch synthesis catalysts [7,8], noble metal ruthenium-based catalysts [9,10], and molybdenum sulfide-based catalysts [11,12]. Among these catalyst systems, the modified methanol synthesis catalyst mainly produced methanol with a lower C 2+ OH selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the higher alcohols, after separation and purification, can serve as feed stocks for value-added fine chemicals, demonstrating a wide application prospect [4]. Generally, the catalytic production process for higher alcohols synthesis from syngas needs to occur over the solid catalysts, which are roughly classified into the following four categories: modified methanol synthesis catalysts [5,6], modified Fischer-Tropsch synthesis catalysts [7,8], noble metal ruthenium-based catalysts [9,10], and molybdenum sulfide-based catalysts [11,12]. Among these catalyst systems, the modified methanol synthesis catalyst mainly produced methanol with a lower C 2+ OH selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…3b, H 2 -TPR profile of CuO/Al 2 O 3 (before test) reveals the presence of a reduction peak at 300 °C corresponding to the reduction of CuO. After test, we noticed a decrease in the intensity of this peak at 300 °C and the formation of another two reduction peaks at 600 °C and 800 °C approximately which correspond to the reduction of CuAl 2 O 4 and CuAlO 2 respectively [28]. Such incorporation of copper into the support lattice can be due to high interaction between CuO and alumina at high temperature.…”
Section: Resultsmentioning
confidence: 78%
“…In light of the above aspects, the present Special Issue is mainly focused on the fabrication and fine-tuning of NMs-free metal oxide catalysts by means of advanced synthetic and/or promotional routes. It consists of fourteen high quality papers, involving: a comprehensive review article on the recent advances on the rational design and fine-tuning of ceria-based metal oxide catalysts [5]; two articles on the ceria nanoparticles morphological effects on N 2 O decomposition [14] and CO oxidation [10] over ceria-based binary oxides; two articles on NO decomposition over K-promoted Co-Mn-Al mixed oxides [34,35]; one article on the effect of ceria synthesis methods on the carbon pathways in dry reforming of methane (DRM) over Ni/CeO 2 catalysts [36]; one article on the impact of synthesis procedure and aliovalent doping in Co-Al spinel-type oxides for lean methane combustion [37]; one article on the support effect on the direct conversion of syngas to higher alcohols over copper-based oxides [38]; one article on nanofibrous Ni/Al 2 O 3 catalysts prepared by electrospinning for methane partial oxidation [39]; one article on the influence of precursor compounds on the selective catalytic reduction (SCR) of NO x by NH 3 over FeMgO x oxides [40]; one article on the synthesis and active sites determination of ZrO 2 -supported WO x solid acid catalysts [41]; one article on the synthesis and electrocatalytic performance of RuO 2 nanoparticles [42]; one article on the fabrication and photocatalytic performance of mesoporous frameworks of ZnFe 2 O 4 (ZFO) and MnFe 2 O 4 (MFO) nanoparticles [43]; and one article on the synthesis of polymer supported catalysts for arylamination reaction [44].…”
Section: This Special Issuementioning
confidence: 99%
“…X. Li et al [38] reported on the impact of support nature (SiO 2 , Al 2 O 3 ) and alkali promotion (K) on the synthesis of higher alcohols from CO hydrogenation over Cu-based catalysts. Significant differences on CO conversion and product's selectivity were revealed, attributed to support-and alkali-induced effects on redox and electronic properties.…”
Section: Contribution Highlightsmentioning
confidence: 99%